1966
DOI: 10.1136/gut.7.6.671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological study of vagotomy and gastric drainage in the treatment of pyloric stenosis due to duodenal ulceration.

Abstract: EDITORIAL COMMENT Twenty-one patients with pyloric stenosis treated by vagotomy and gastric drainage have been followed up clinically and radiologically for periods of between nine months and five years from operation. Results are uniformly good and the method is advocated as the surgical treatment of choice for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Postoperative gastric retention did not occur in any of the patients and none required postoperative gastric aspiration. All had good functional results, and subsequent barium meal examinations showed return of the dilated stomachs to normal size and tone with satisfactory emptying [8]. At present, our total has reached 80 patients and, to date, apart from 1 patient who developed a stomal ulcer and required subsequent conversion to partial gastrectomy, the results have been uniformly satisfactory.…”
Section: Surgical Treatmentmentioning
confidence: 72%
“…Postoperative gastric retention did not occur in any of the patients and none required postoperative gastric aspiration. All had good functional results, and subsequent barium meal examinations showed return of the dilated stomachs to normal size and tone with satisfactory emptying [8]. At present, our total has reached 80 patients and, to date, apart from 1 patient who developed a stomal ulcer and required subsequent conversion to partial gastrectomy, the results have been uniformly satisfactory.…”
Section: Surgical Treatmentmentioning
confidence: 72%
“…Seventy-four per cent of patients were found to have achieved perfect clinical results after HSV, whereas only 44% of patients after TV + D did so: 94 % of patients had good-or-excellent results (Visick grades 1 + 2) after HSV, compared with only 74 % of patients after TV + D. These findings, while they might appear at first sight to give an unfair account of the clinical results to be expected after TV + D (Feggetter and Pringle, 1965;Ellis et al, 1966), are, in fact, very similar to those which were reported previously from Leeds after HSV and TV + D when these procedures were used in the treatment of patients with uncomplicated duodenal ulceration (Goligher et al, 1968;Amdrup et al, 1974). The comparison between HSV and TV + D in this study is greatly weakened, however, by the facts that patients were not allotted in random manner to one or other of the operative procedures and that the length of follow-up of patients after HSV (24 months) was considerably shorter than that of patients who had undergone TV + D (41 months).…”
Section: Discussionmentioning
confidence: 98%
“…Given the likelihood of spontaneous resolution and the disappointing results of early reoperation, there seems to be little indication for early intervention in the majority. A contrast orted5, 7,9,[13][14][15] study can still be justified, however, as it may exclude a mechanical problem such as small bowel obstruction or intussusception of the stoma.…”
Section: Discussionmentioning
confidence: 99%